Modern Directions of Increasing Competitiveness in The International Market on The Example of Guangzhou Goldshine Tech Co., Limited - Weichang Shi; Raju Mohammad Kamrul Alam (Communications of International Proceedings, 2021)
In the context of the global economic crisis caused by the pandemic and as a result of this increased competition for each company, the task of maintaining and increasing its own competitiveness comes to the fore. The market situation largely depends on the state and results of the competition. Business owners attach great importance to analyzing their strengths and weaknesses in order to assess the real possibilities in competition and develop measures and means through which the company could increase its competitiveness. The competitiveness of a company is determined in the stability of its position in the market, the ability to manufacture products that are in demand and to obtain targeted and stable end results. The problem of increasing the company's competitiveness in international markets is becoming especially urgent. The need to enter foreign markets and the natural limitation of sales markets in the domestic market requires a company to seek or create competitive advantages, on which the growth of competitiveness and effective activity in international markets depend. The goal was set in the article: to develop modern directions for increasing the competitiveness of an international company in the international market. For this, the following tasks were set: based on theoretical material, consider approaches to the concept of competition and the competitive position of a company in the international market; study competitive strategies in the international market; analyze Guangzhou Goldshine Tech Co., Limited in the international market; proposals to improve the competitiveness of the company.
Keywords: Competition; Competitive Advantages; Strategies; International Market; Opportunities; Demand.